Impact of aortic repair based on flow field computer simulation within the thoracic aorta - Filipović, Nenad; Milasinovic, Danko; Zdravkovic, Nebojsa; Böckler, Dittmar; Tengg-Kobligk, Hendrik von (Computer methods and programs in biomedicine, 2011)
Purpose of this computational study is to examine the hemodynamic parameters of velocity fields and shear stress in the thoracic aorta with and without aneurysm, based on an individual patient case and virtual surgical intervention. These two cases, case I (with aneurysm) and II (without aneurysm), are analyzed by computational fluid dynamics. The 3D Navier-Stokes equations and the continuity equation are solved with an unsteady stabilized finite element method. The vascular geometries are reconstructed based on computed tomography angiography images to generate a patient-specific 3D finite element mesh. The input data for the flow waveforms are derived from MR phase contrast flow measurements of a patient before surgical intervention. The computed results show velocity profiles skewed towards the inner aortic wall for both cases in the ascending aorta and in the aortic arch, while in the descending aorta these velocity profiles are skewed towards the outer aortic wall. Computed streamlines indicate that flow separation occurs at the proximal edge of the aneurysm, i.e. computed flow enters the aneurysm in the distal region, and that there is essentially a single, slowly rotating, vortex within the aneurysm during most of the systole. In summary, after virtual surgical intervention in case II higher shear stress distribution along the descending aorta could be found, which may produce more healthy reactions in the endothelium and benefit of vascular reconstruction of an aortic aneurysm at this particular location.
Online verfügbar: 12. Februar 2011
Gesehen am 27.10.2022